BUKU CERITA BERKUALITAS KEARIFAN LOKAL BALI DALAM BENTUK FLIPBOOK MAKER UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 5 SD - Suryani, Komang; Putrayasa, Ida Bagus; Sudiana, I Nyoman (Jurnal Administrasi Pendidikan Indonesia, 2024)
The low reading skills of students are an important problem that must be solved. This research aims to develop a storybook containing local Balinese wisdom based on flipbooks as an interactive and effective learning medium in improving cultural literacy and character education of elementary school students. This storybook is designed to integrate Balinese cultural values, such as tolerance, mutual cooperation, and harmonious relationship with nature, into engaging and meaningful learning. The flipbook  format was chosen for its ability to combine visual, audio, and interactive elements, which provides a more enjoyable learning experience compared to conventional media. This research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The results of validation by experts show that flipbook-based storybooks are of high quality in terms of content, visual design, and learning effectiveness. Implementation trials in elementary schools showed that students who learned using flipbook-based storybooks experienced significant improvements in material comprehension, learning motivation, and cultural literacy skills compared to students who used conventional learning methods. The results of this study confirm that flipbook-based storybooks are effective in supporting interactive learning, improving cultural literacy, and shaping students' characters. By integrating digital technology and local wisdom, this media provides innovative solutions that are relevant to the needs of education in the era of globalization